2023
DOI: 10.1101/2023.03.01.530592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-scale requirements for dynein-based trafficking revealed by a high-content arrayed CRISPR screen

Abstract: The cytoplasmic dynein-1 (dynein) motor plays a key role in cellular organisation by transporting a wide variety of cellular constituents towards the minus ends of microtubules. However, relatively little is known about how the biosynthesis, assembly and functional diversity of the motor is orchestrated. To address this issue, we have conducted an arrayed CRISPR loss-of-function screen in human cells using the distribution of dynein-tethered peroxisomes and early endosomes as readouts. From a guide RNA library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 117 publications
1
4
0
Order By: Relevance
“…However, our data support a model where TGN38/46 dispersion into endosomes is a consequence of cellular stress rather than a feature of NLRP3 activation, in agreement with recent studies [58][59]. Further supporting this conclusion, a phenotypic CRISPR screen demonstrated that many cellular perturbations of transport likely unrelated to NLRP3 activation induce TGN38/46 peripheral redistribution [171].…”
Section: Ipssupporting
confidence: 93%
“…However, our data support a model where TGN38/46 dispersion into endosomes is a consequence of cellular stress rather than a feature of NLRP3 activation, in agreement with recent studies [58][59]. Further supporting this conclusion, a phenotypic CRISPR screen demonstrated that many cellular perturbations of transport likely unrelated to NLRP3 activation induce TGN38/46 peripheral redistribution [171].…”
Section: Ipssupporting
confidence: 93%
“…1A). For optimal gene disruption, we used a lentiviral gene delivery system and 3 guide RNAs per gene – a method also used by others to increase the frequency of gene disruption 16 . We applied the LTP knockout library to MelJuSo, a human melanoma cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting and non-targeting guide sequences (Supplementary Table 1) were obtained from the Brunello Human CRISPR Knockout Pooled Library [https://www.addgene.org/pooled-library/broadgpp-humanknockout-brunello/ ; 26780180] and cloned into lentiCRISPR v2 plasmid [https://www.addgene.org/52961/ ; 25075903] as described previously 36 . To increase the efficiency of the gene disruption, we used 3 guide RNAs per gene -a method also used by others to increase the frequency of gene disruption 37 . Cloning of guide RNAs were individually confirmed by Sanger sequencing.…”
Section: Library Design and Generationmentioning
confidence: 99%
“…As a positive control, we used a GFP-BICD2N MTS line expressing the constitutively active N-terminal fragment of BICD2 (residues 1-400, BICD2N), which is known to elicit dynein-based motility and has been used extensively in organelle relocation assays (Supplementary Fig. 1B) 25,26,28 . GFP MTS expression did not alter the distribution of mitochondria, which remained scattered in the cytoplasm as observed in wild type cells (Fig.…”
Section: The Bacterial Protein Scac Recruits the Activating Adaptors ...mentioning
confidence: 99%
“…1C) 25,26 . An accumulation of mitochondria at the perinuclear region provides evidence that the candidate protein is a dynein effector 25,27,28 . We generated Flp-in T-REX HeLa cell lines expressing GFP MTS or GFP-ScaC MTS fusion proteins.…”
Section: The Bacterial Protein Scac Recruits the Activating Adaptors ...mentioning
confidence: 99%